What Makes a Difference in Patient Safety when Designing, Implementing and Evaluating Clinical Decision Support Systems?. (November 2019) - Ozkaynak, Mustafa; Bisantz, Ann; Militello, Laura; Miller, Kristen; Rayo, Michael; Slagle, Jason
Clinical decision support (CDS) has become an important component of all health settings. Despite a long history of research on their design and implementation, their use is still suboptimal. Unique characteristics of specific settings can require highlighting different features and design recommendations for CDS. This panel will focus on various pitfalls in designing and implementing CDS in various clinical settings and strategies to overcome these pitfalls. Each panelist will introduce their work by discussing the design and implementation challenges that prevent achieving the targeted patient and organizational outcomes. Panelists will also discuss potential approaches with their strengths and limitations to address these challenges. The panelists will then interact with audience members to solicit users' (e.g. clinicians, patients) unfulfilled needs and limitations of existing approaches to create a broad future research agenda at the intersection of human factors approaches and theories, and CDS systems.